Effect of Synthetic Bone Graft Substitutes in Management of Nonunion in Long Bones: A Case Series - Muthamilselvan Kumanan; Manikandan Navaneethakrishnapandian; Mohamed Ibrahim (Journal of Orthopedics and Joint Surgery)
Introduction: Treating nonunion is a major concern for any orthopedic surgeon. Preparation of autograft for use in nonunion itself is associated with various complications, starting from donor site morbidities to postoperative wound infections. To overcome these complications, an artificial substance that is biocompatible, which mimics all the properties of an autograft, may be an ideal thing for the management of nonunion. One such thing that was put forth in our study is “Synthetic Bone Graft.” All the pros and cons and their effectiveness in today's modern orthopedic management of nonunion are discussed below. Aim: To evaluate the efficacy and outcome of synthetic bone grafting substances in the management of nonunion in long bones. Materials and methods: This is a cross-sectional study. Patients with noninfected nonunion are selected. A total of 20 patients were treated with specific fracture fixation augmented with synthetic bone grafts and were followed for about 18 months in the Department of Orthopaedics, Tirunelveli Medical College Hospital, Tirunelveli, Tamil Nadu, India. Results and discussion: In our study of 20 cases with nonunion of long bones, 90% of cases (18 cases out of 20 cases) showed clinical and radiological union among our case study. A bone substitute with the composition of tricalcium phosphate and calcium sulfate is used in our study. Functional and radiological outcomes of synthetic bone graft materials in the management of nonunion in long bones showed far better results compared to other bone graft materials. In the future, the use of these synthetic bone graft materials in bone regeneration under specific indications and with safety roles will simulate the normal bone formation cascade with reduced morbidity and cost in the long-term.